Phonological fossilisation of EFL learners: the interference of phonological and orthographic system of L1 Javanese - Senowarsito,; Sukma Nur Ardini, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper discusses the interference of phonological and orthographic systems of the mother tongue on phonological fossilisation of English on Foreign Language learners in Javanese contexts. 25 fourth-semester university students were selected as respondents. The data were collected by means of pre-test and post-test on pronouncing isolated words, continuous speeches, and reading aloud on manipulated short text. Contrastive analysis reveals that the phonological fossilisation among Javanese students commonly occurred in continuous speech rather than isolated words when they pronounced vowels /æ/, /ɪ/, /əә/, /ʌ/, /i:/ in initial and middle position; diphthongs /əәʊ/, /eɪ/, /aʊ/ in initial and middle; as well as consonants /dʒ/, /ʧ/, /θ/, /ð/, /ʃ/, /v/, /ʒ/, /z/, /k/, /t/ in initial, middle and final ones. The students tended to omit ‘/θ/’,‘/d/ and /t/’in final position, ‘consonant clusters in initial, mid, final position’, and /j/ after plosive bilabial’. Those phonological fossilisations were due to the interference of the phonological and orthographic systems of their mother tongue.